Economics Teachers’ Awareness and Readiness Towards the Use of Podcasting for Teaching and Learning in Bodinga Local Government, Sokoto State-Nigeria - Ismaila Abdullahi Abubakar; Mallam Abubakar Aliyu; Umar Faruk Husaini; Ba Luan Tran (Advanced Journal of STEM Education, 2023)
This study investigated the economics teacher’s awareness and readiness toward the use of podcasting for teaching and learning in secondary schools in Bodinga’s local government area of Sokoto state, Nigeria. Descriptive survey research was used. Qualitative saved as a mode of data collection. The populations of the study were all from secondary schools in Bodinga local government area, the sample was drowned from four secondary schools in Bodinga local government, Sokoto state Nigeria. Eight economics teachers were used as samples, two from each secondary school. Three objectives and three research questions were formed to guide the study. Data Blank was used as an instrument for data collection, developed by the researchers. The instrument has two parts, A and B, part A is for demographic information by the respondents, while part B contained items on teachers’ awareness and readiness towards the use of podcasts for teaching and learning. The data obtained was analyzed. Results of the study showed that economics teachers are not aware of the use of podcasts for teaching and learning. It also revealed that economics teachers are ready to use podcasting in their teaching and learning. Economics teachers have no knowledge and skills regarding the use of Podcasting. The study recommends that economics teachers be mobilized and educated/trained on the use of podcasting for teaching and learning in secondary schools to improve teaching and learning.